The Analysis of Changes in Calorific Value of Coal in the Coal Flow Coal Feeder and Net Plant Heat Rate (NPHR) - Djaeni, Mohammad; Windarta, Jaka; Muqorrobin, Rifqi (ASTONJADRO, 2025)
This study to determine the effect in the difference of coal calori value on power plants. Currently, coal-fired power plants dominate power plants in Indonesia with 42.38%. With the dominance of coal-fired power plants, the need for coal in Indonesia remains high. In the electricity production process, calori value is an important in the electricity production process. This study discusses the effect of coal on power plants. In this study, coal received two types of treatment, namely by heating with sunlight and oven. Then in this study, research was conduct on the calori value of coal on several parameters such as Specific fuel consumption (SFC), coal flow, boiler efficiency and NPHR. From the results of the research conduct, the drying process in the sun for 10 days can reduce the water content by 28% and reduce the weight of coal from 150 grams to 108 grams. Changes in calories due to a reduction in the water content value in coal by 28% to 5414 kcal / kg. In the coal combustion test, the calorific value of coal is inversely proportional to the NPHR value and coalflow of the PLTU.